De tirano a vítima: o conflito da legitimidade monárquica em Ricardo II e a inversão da percepção sobre o rei - Uszacki, Wladimir D'Ávila (2022)
This research aims to deepen the understanding of tyranny in Richard II, in how the author depicts the character as a tyrant, and, throughout the play, this depiction is inverted, and Richard becomes a victim, so much that it is possible to interpret him as a martyr. We organized the according to the chronological order of the play, first analysing the formality of the king and how he uses and depends on protocol to represent and show his royal power. The research, then contextualizes the English Renaissance understanding of authority, Divine Right and the concepts of order and hierarchy in the elizabethan world, the context in which Shakespeare was raised and produced his plays, and how these ideologies are present in the play. With such data in hand, we proceed to the thorough character and circumstance analysis, first on how Richard is seen and shown to be an autocrat, a tyrant ruled by will. Developing these portrayals allows us to identify linguistic markers in the characters’ discourses that show different forms of designing monarchical power, its authority and its limits, and how Richard crosses those limits, leading to his decline. We immediately identify the character’s loss of control, spiraling in despair for the loss of his authority, but a growing self-affirmation of his authority as product of supernatural design. We finally analyse the deposition scene and how Richard shows he acknowledges all nuances of politics, which he previously ignored, and use them in his discourse against his rivals, seeing in them apparent hypocrisy, hidden interests. His prison reveals a growing victimization of the character, forcibly separated from his family and everyone, he sees in his rivals ambition and greed, foretelling future divions and recognizing in himself authority given by providence, removing from within traces of uncertainty and doubt that made him indecisive, and dies fighting one last time for himself and his crown and what it represents. We conclude the research bringing the main analysis points and the ways the play depicts authority, villainy, how Shakespeare builds a universe where no one is entirely right or wrong, and all are influenced by truly human interests, closing with possibilities for further research.